(untitled) (Huellas, 2015)
This article discusses the socio- economic representativeness of the municipality of Confresa, in the region of Araguaia, North of Mato Grosso, and its role in regional development. On the basis of concepts such as centrality and urban bias, this work aims at understanding how the socio - economic and political relations develop, in comparison with the situation of other surrounding districts. In this sense, it aimed to examine the representativeness of the small towns in the regional development scenario that is described as part of the State ofMato Grosso. Moreover, small Amazonian cities have been analyzed on the basis of socio-economic and political processes because they are places in which life styles differ significantly from other urban regions of Brazil. The article approaches the historical birth of the city, the role of settlers and early inhabitants, and their struggle for survival and continuity along time. From a conceptual point of view, we attempted to discuss the small town and its implementation in the Brazilian political context and how Confresa fits this discussion.